Educational Program Evaluation using CIPP Model - Warju, Warju (INVOTEC, 2016)
There are many models of evaluation that can be used to evaluate a program. However, the most commonly used is the context, input, process, output (CIPP) evaluation models. CIPP evaluation model developed by Stufflebeam and Shinkfield in 1985. The evaluation context is used to give a rational reason a selected program or curriculum to be implemented. A wide scale, context can be evaluated on: the program's objectives, policies that support the vision and mission of the institution, the relevant environment, identification of needs, opportunities and problems specific diagnosis. Evaluation input to provide information about the resources that can be used to achieve program objectives. Evaluation inputs used to: find a problem solving strategy, planning, and design programs. Evaluation process serves to provide feedback to individuals to account for the activities of the program or curriculum. The evaluation process is conducted by: monitoring sources can potentially cause failure, prepare a preliminary information for planning decisions, and explain the process that actually happened. Product evaluation measure and interpret the achievement of goals. Evaluation of the products also come to: the measurement of the impact of the expected and unexpected. The evaluation is conducted: during and after the program. Stufflebeam and Shinkfield suggest product evaluation conducted for the four aspects of evaluation: impact, effectiveness, sustainability, and transportability. The decision making process is done by comparing the findings / facts contained in context, input, process and product standards or criteria that have been set previously.